Jackson Elementary School Christmas Show - Watkins, Howard::::::::: (1983)
Kindergarten class on stage; Adam Watkins front center in light green suit; teacher LeAnne Wiens in purple dress Devon Bleile-Kratzer in back row center in red and green vest